2022
DOI: 10.1007/s11695-022-05947-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Symptomatic Gallstone Disease and Gallstone Formation After Bariatric Surgery

Abstract: Purpose Patients who undergo bariatric surgery are at risk for developing cholesterol gallstones. We aimed to identify risk factors that are associated with symptomatic gallstone disease and gallstone formation after bariatric surgery. Materials and Methods We included participants of the UPGRADE trial, a multicenter randomized placebo-controlled trial on the prevention of symptomatic gallstone disease with ursodeoxycholic acid (UDCA) after bariatric surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Caucasians were defined as exposed, and other races were defined as nonexposed. Three articles evaluated whether race is a risk factor for cholelithiasis after bariatric surgery [ 20 , 24 , 30 ] There was no heterogeneity among the studies (I 2 = 0%, P = 0.84), so a fixed-effects model was used for the meta-analysis. The results showed that white race was a risk factor for cholelithiasis after bariatric surgery [OR = 1.62, 95% CI (1.19, 2.19), P = 0.002].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Caucasians were defined as exposed, and other races were defined as nonexposed. Three articles evaluated whether race is a risk factor for cholelithiasis after bariatric surgery [ 20 , 24 , 30 ] There was no heterogeneity among the studies (I 2 = 0%, P = 0.84), so a fixed-effects model was used for the meta-analysis. The results showed that white race was a risk factor for cholelithiasis after bariatric surgery [OR = 1.62, 95% CI (1.19, 2.19), P = 0.002].…”
Section: Resultsmentioning
confidence: 99%
“…This research examined two surgical procedures, RYGB and SG, and defined RYGB as exposure and SG as nonexposure. A total of 10 articles [ 16 20 , 23 , 25 , 30 32 ] investigated whether the surgical procedure is a risk factor for cholelithiasis after bariatric surgery. There was moderate heterogeneity (I 2 = 66%, P = 0.002), so a random-effect model was used for the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient gallbladder motility contributes to cholesterol gallstone formation and is impaired under many risk factors for cholesterol gallstone formation, such as pregnant women, obese patients, and their rapid weight loss, diabetes mellitus, and patients receiving total parenteral nutrition[ 63 ]. A recent study showed that 78 of 959 patients (8%) who underwent laparoscopic Roux-en-Y gastric bypass (RYGB) or sleeve gastrectomy developed symptomatic gallstone disease within 24 mo[ 64 ]. In patients without gallstones before RYGB surgery, ursodeoxycholic acid treatment reduced the occurrence of symptomatic gallstone disease compared with placebo[ 65 ].…”
Section: Cholesterol Gallstone Formation By Impaired Gallbladder Moti...mentioning
confidence: 99%
“…The recurrence rates of common bile duct (CBD) stones vary across different studies, but range from 4-24% (4). Research has confirmed that the reasons for gallstone formation are aberrant metabolism and the secretion of cholesterol and bile acids (5). Currently, a sphincter of Oddi laxity (SOL) is considered an important factor in cholangiolithiasis occurrence.…”
Section: Introductionmentioning
confidence: 99%